Seed dispersal and realized gene flow of two forest orchids in a fragmented landscape - Kotilínek, M; Těšitelová, T; Košnar, J; Fibich, P; Hemrová, L; Koutecký, P; Münzbergová, Z; Jersáková, J (Plant biology (Stuttgart, Germany), 2020)
Species with vast production of dust-like windborne seeds, such as orchids, should not be limited by seed dispersal. This paradigm, however, does not fit recent studies showing that many sites suitable for orchids are unoccupied and most seeds land close to their maternal plant. To explore this issue, we studied seed dispersal and gene flow of two forest orchid species, Epipactis atrorubens and Cephalanthera rubra, growing in a fragmented landscape of forested limestone hills in southwest Bohemia, Czech Republic. We used a combination of seed trapping and plant genotyping methods (microsatellite DNA markers) to quantify short- and long-distance dispersal, respectively. In addition, seed production of both species was estimated. We found that most seeds landed very close to maternal plants (95% of captured seeds were within 7.2 m) in both species, and dispersal distance was influenced by forest type in E. atrorubens. In addition, C. rubra showed clonal reproduction (20% of plants were of clonal origin) and very low fruiting success (only 1.6% of plants were fruiting) in comparison with E. atrorubens (25.7%). Gene flow was frequent up to 2 km in C. rubra and up to 125 km in E. atrorubens, and we detected a relatively high dispersal rate among regions in both species. Although both species occupy similar habitats and have similar seed dispersal abilities, C. rubra is notably rarer in the study area. Considerably low fruiting success in this species likely limits its gene flow to longer distances and designates it more sensitive to habitat loss and fragmentation.
Keywords: seed dispersal; Gene Flow; Cephalanthera rubra; gene flow; Orchidaceae; šíření semen; fragmented landscape; tok genů; seed traps; Epipactis atrorubens; Seed Dispersal; microsatellite DNA markers; ekosystém; Ecosystem